Language learning using texting and wiki: a Malaysian context - Osman, Mashanum; Chung, Paul W.H. (2011)
This paper describes a study that has been carried out to examine the effect and use of mobile and communication technologies for learning English, which is a second language in the Malaysian context. Two of the main objectives of this study are to design learning activities that involve the use of mobile and communication technologies that would help improve students’ communication and collaboration skills in group activities and to evaluate the effects of using these technologies in the learning process. The study uses the quasi experimental approach to gather data and obtain feedback from a sample of first year undergraduate students in a public Malaysian university. The instruments used in this student include pre and post questionnaires, pre and post writing tests, texting, and updating learning activities using wiki. Learning activities were designed which include participants’ use of their mobile phones for texting and the use of computer to collaborate in a group using the wiki software. Participants received text messages at regular intervals and were expected to reply to some of those messages that were quizzes. The messages were of six different types which are update reminder, lesson reminder, general quiz, topic quiz, grammar quiz and resources. A wiki website was also set up for the participants to collaborate with members in their group by updating the relevant lessons. The study concludes that the use of mobile phones with suitable learning activities is favoured and it helps improve the participants’ learning experience. On the other hand Malaysians are not well acquainted with wiki technologies and its use has a negative effect on their learning experience.